The influence of leadership, career development, and organizational culture on organizational citizenship behaviors mediated by organizational commitment in Sub-District in Merauke District - Lomo, Agustina; Erari, Anita; Handoyo, Sarwo Edy (Technium Business and Management, 2024)
The research objective is to determine the Influence of leadership, career development, and organizational culture on organizational citizenship behaviors mediated by organizational commitment in the District of Merauke. The research employs a quantitative research approach. The research sample consists of all Sub-District employees, totaling 120 people. The questionnaire results are tabulated and analyzed using Structural Equation Modeling (SEM) through the SmartPLS application. The analysis results demonstrate that leadership style, organizational culture, and organizational commitment have a positive and significant influence on OCB. However, organizational commitment has a negative and significant influence on OCB. Leadership style and career development have a positive but not significant influence on organizational commitment. In contrast, organizational culture has a positive and significant influence on organizational commitment. Organizational commitment does not mediate the influence of leadership style and career development on OCB. However, organizational commitment significantly mediates the relationship between organizational culture and OCB.